Remyelination Therapy in Multiple Sclerosis - Harlow, Danielle E.; Honce, Justin M.; Miravalle, Augusto A. (Frontiers in Neurology, 2015)
Multiple Sclerosis (MS) is an immune-mediated disorder of the central nervous system that results in destruction of the myelin sheath that surrounds axons and eventual neurodegeneration. Current treatments approved for the treatment of relapsing forms of MS target the aberrant immune response and successfully reduce the severity of attacks and frequency of relapses. Therapies are still needed that can repair damage particularly for the treatment of progressive forms of MS for which current therapies are relatively ineffective. Remyelination can restore neuronal function and prevent further neuronal loss and clinical disability. Recent advancements in our understanding of the molecular and cellular mechanisms regulating myelination, as well as the development of high throughput screens to identify agents that enhance myelination, have lead to the identification of many potential remyelination therapies currently in pre-clinical and early clinical development. One problem that has plagued the development of treatments to promote remyelination is the difficulty in assessing remyelination in patients with current imaging techniques. Powerful new imaging technologies are making it easier to discern remyelination in patients, which is critical for the assessment of these new therapeutic strategies during clinical trials. This review will summarize what is currently known about remyelination failure in MS, strategies to overcome this failure, new therapeutic treatments in the pipeline for promoting remyelination in MS patients, and new imaging technologies for measuring remyelination in patients.